The Impact of the Closing of the Jordanian Borders with Iraq and Syria on the Jordanian Economy by Using ARDL Model - Al-Majali, Ahmad; Al-Tarawneh, Qusay (Jordan Journal of Economic Sciences, 2019)
This study aims to examine the effect of the Jordanian geographical borders closure with Syria and Iraq on the Jordanian trade over the period 2008-2006, using monthly data. The study used the autoregressive distributed lag (ARDL) and the open-bound techniques to estimate the model. The results provide empirical evidence supporting the existence of a long-run relationship between the study variables suggesting that the closure of borders has negative impact on the total trade and exports to the neighboring countries. This adverse effect been reflected in deteriorating the index of industrial production which declined by 3.32 points. In addition, the study provided empirical evidence confirming the adverse effect of the closure on the total trade and exports in the short run.